INCREASED PHOTORECEPTOR OUTER SEGMENT VOLUME FOLLOWING SYSTEMIC TREATMENT OF BIRDSHOT CHORIORETINOPATHY. Issue Volume 14:Issues 1(2020) (2020) - Docherty, Gavin; Martens, Rosanna; Forooghian, Farzin
Abstract : Purpose: Retinal degeneration in birdshot chorioretinopathy can be quantified using spectral domain optical coherence tomography by measuring the photoreceptor outer segment (PROS) volume. The purpose of this study was to determine if the PROS volume in BSCR responds to systemic immunomodulatory therapy (IMT). Methods: Retrospective chart review with analysis of PROS volume derived from spectral domain optical coherence tomography. Results: We identified a total of three patients who met our inclusion criteria. At baseline, all patients had abnormal PROS and/or ellipsoid layer findings on spectral domain optical coherence tomography. After systemic immunomodulatory therapy, these abnormalities improved, and PROS volume increased, in all patients ( P < 0.05). Conclusion: PROS volume can increase after systemic treatment of birdshot chorioretinopathy. This SD-OCT parameter may serve as a useful marker of retinal degeneration in BSCR, and may be a useful outcome measure in monitoring treatment response in birdshot chorioretinopathy. Abstract : The authors report that photoreceptor outer segment volume increases after systemic treatment in birdshot chorioretinopathy.